Development of a Multiplex Quantitative PCR for Detecting Porcine Epidemic Diarrhea Virus, Transmissible Gastroenteritis Virus, and Porcine Deltacoronavirus Simultaneously in China - Jianpeng Chen; Rongchao Liu; Huaicheng Liu; Jing Chen; Xiaohan Li; Jianfeng Zhang; Bin Zhou (Veterinary Sciences, 2023)
Porcine epidemic diarrhea virus (PEDV), transmissible gastroenteritis virus (TGEV), and porcine deltacoronavirus (PDCoV) belong to the category of swine enteric coronavirus that cause acute diarrhea in piglets, which has resulted in massive losses to the pig husbandry. Therefore, a sensitive and rapid detection method which can differentially detect these viruses that lead to mixed infections in clinical cases, is urgently needed. According to the conserved regions of the PEDV M gene, TGEV S gene, and PDCoV N gene, and the reference gene of porcine (β-Actin), we designed new specific primers and probes for the multiplex qPCR assay capable of simultaneously detecting three RNA viruses. This method, with a great specificity, did not cross-react with the common porcine virus. Moreover, the limit of detection of the method we developed could reach 10 copies/μL ,and the intra- and inter-group coefficients of variation of it below 3%. Applying this assay to detect 462 clinical samples which were collected in 2022–2023, indicated that the discrete positive rates of PEDV, TGEV, and PDCoV were 19.70%, 0.87%, and 10.17%, respectively. The mixed infection rates of PEDV/TGEV, PEDV/PDCoV, TGEV/PDCoV, and PEDV/TGEV/PDCoV were 3.25%, 23.16%, 0.22%, and 11.90%, respectively. All in all, the multiplex qPCR assay we developed as a tool for differential and rapid diagnosing can be put on the active prevention and control of PEDV, TGEV, and PDCoV, , which can create great value in the diagnosis of swine diarrhea diseases.